Novel peptides functionalized gold nanoparticles decorated tungsten disulfide nanoflowers as the electrochemical sensing platforms for the norovirus in an oyster. (August 2020) - Baek, Seung Hoon; Park, Chan Yeong; Nguyen, Thang Phan; Kim, Min Woo; Park, Jong Pil; Choi, Changsun; Kim, Soo Young; Kailasa, Suresh Kumar; Park, Tae Jung
Abstract: Human norovirus is one of the potential foodborne pathogens causing acute gastroenteritis, diarrhea, and food poisoning. For norovirus detection, we developed the norovirus specifically capturable peptides functionalized gold nanoparticles (AuNP) decorated tungsten disulfide nanoflower (WS2 NF/AuNP). Based on the 3D-structured WS2 NF acting as a supporting material, AuNP were immobilized on its surface to assist the conductivity of WS2 NF and provide effective immobilization sites for bioreceptors. Since norovirus is composed of protein that functions as an insulant, as the virus bind with WS2 NF/AuNP, the impedance is elevated by hindering the charge transfer between the working electrode and redox species ([Fe(CN)6 ] 3-/4- ). The prepared nano-bio hybrid sensor was assessed by electrochemical impedance spectroscopic technique with spiked samples and deliberately infected oyster samples, respectively. In the case of the former, the electrochemical sensor represents a low detection limit (2.37 copies/mL) with a detection range from negative control to 10 4 copies/mL, and it was shown a detection limit of 6.21 copies/mL even in the oyster samples. Besides, when it applies to the different types of viruses such as rotavirus and dengue virus to verify the selectivity of this system, there were no effective signals except the norovirus. Therefore, it revealed that combining WS2 NF and AuNP enhances electrochemical activity and stability via mutual synergetic effects. Highlights: Flower-shaped WS2 (WS2 NF) synthesized for electrochemical sensing. The surface of WS2 NF decorated with gold nanoparticles (AuNPs). Norovirus-specific binding peptide on the WS2 NF/AuNPs. Low detection limit in spiked (2.37 copies/mL) and oyster samples (6.21 copies/mL). Selective response within 60 min compared with other viruses.